Characterization of Some Spelt Wheat Starches as a Renewable Biopolymeric Material. (5th February 2014) - Gałkowska, Dorota; Witczak, Teresa; Korus, Jarosław; Juszczak, Lesław
Abstract : The aim of this work was to analyze selected physical, chemical, thermal, and rheological properties of starches isolated from different spelt wheat varieties. The analyzed starches contained from 22.5 to 24.6 g/100 g of amylose and from 45.9 to 50.6 mg/100 g of phosphorus. Ranges of characteristic gelatinization temperatures, T O, T P, andT E, were 55.7–58.5°C, 61.1–62.6°C, and 67.4–68.2°C, respectively, while gelatinization enthalpy ranged from 8.87 to 9.96 J/g. The pasting curves showed significant differences in pasting characteristics of the starches. The values of maximum viscosity (η m a x ) and viscosity after cooling (η 50 ) determined for the starch pastes were in the range of 82.3–100.7 B.U. and 149.3–172.7 B.U., respectively. The starch pastes demonstrated non-Newtonian, shear thinning flow behaviour and thixotropy phenomenon. After cooling the resulting starch gels were characterized by different viscoelastic properties, with a dominance of elastic features (G ′ > G ′′ ). The starches exhibited different tendency to retrogradation, with its degree (R = Δ H R / Δ H G ) in the range of 21.1–37.4%.